Levels of apolipoproteins as risk factors for coronary artery disease - Ashmaig,Mohmed (2011)
INTRODUCTION: The Saudi population is renowned for their unhealthy diet and physical inactivity. OBJECTIVE:To investigate apolipoproteins B (apo B), A-I (apo A-I) and B/A-I as risk factors that might be associated with increased incidence of the coronary artery disease. METHODS: Two hundred and twenty subjects suspected of having the coronary artery disease underwent coronary angiography and blood draw following a 12-hour fast. Apolipoproteins B and A-I were both measured by turbidimetric methods. RESULTS: One hundred and forty subjects were positive and 80 subjects were negative for the coronary artery disease. Both apolipoproteins were found to be statistically significant as risk factors for the coronary artery disease: apolipoprotein B (105.33±29.22 versus 94.56±24.35 mg/dL, p<0.003), apolipoprotein A-I (123.98±25.6 versus 133.5±24.1 mg/dL, p<0.004) and apolipoproteins B/A-I (0.88±0.28 versus 0.72±0.2, p<0.0001). CONCLUSIONS:Measurements of apolipoproteins B, A-I and calculation of apolipoproteins B/A-I ratio either instead of or in addition to the customary measurements of lipoprotein cholesterol may significantly add to predicting and assessing the coronary risk factors in the Saudi population.